2001
DOI: 10.2118/01-12-01
|View full text |Cite
|
Sign up to set email alerts
|

Relative Permeability in Dual Porosity Porous Media

Abstract: Reliable relative permeability data is an essential input parameter in reservoir engineering, most significantly in the area of reservoir simulation of dual porosity systems. However, measurements of relative permeability do not work well, because of laboratory limitations. Also, reservoir core samples are generally extracted from zones where induced or natural fractures are absent. Obviously, data obtained from these cores may not reflect the real behaviour of naturally fractured reservoirs. Because of this l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Due the complex flow in shale gas reservoirs, gas desorption in the matrix, gas diffusion from the matrix to natural fractures, Darcy flow in natural fractures and non-Darcy flow in hydraulic fractures are considered in the simulation. In this study, the water and gas flow in shale matrix and fractures are described with two different sets relative permeability curves based on the previous study (Deghmoum et al, 2001;Shanley et al, 2004), as shown in Fig. 2.…”
Section: Simulation Model Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due the complex flow in shale gas reservoirs, gas desorption in the matrix, gas diffusion from the matrix to natural fractures, Darcy flow in natural fractures and non-Darcy flow in hydraulic fractures are considered in the simulation. In this study, the water and gas flow in shale matrix and fractures are described with two different sets relative permeability curves based on the previous study (Deghmoum et al, 2001;Shanley et al, 2004), as shown in Fig. 2.…”
Section: Simulation Model Descriptionmentioning
confidence: 99%
“…Considering the fracturing water injected during the hydraulicfracturing treatment, the water-phase imbibition caused by the capillary pressure between water and gas phases is important in the gas production performance. Based on the empirical correlation (Deghmoum et al, 2001;Shanley et al, 2004), the capillary pressure curve used in the matrix is illustrated in Fig. 3.…”
Section: Simulation Model Descriptionmentioning
confidence: 99%
“…The introduction of this law, i.e. the linearity between pressure gradient and flow rate, in petroleum industry is well recognized as the key factor in reservoir engineering (2) . However, in certain circumstances such as the turbulent flow, this law may lead to erroneous results.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The upper VI-3 unit is overlain by the Gothlandian shale, which has uniform petrophysical properties and thickness. The lower VI-2 unit exhibits rapid changes in both thickness and facies where the depositional environment is mainly of glacial influence 5,6 .…”
Section: Simulation Model On Tft Wellmentioning
confidence: 99%
“…To consider the effect of fracture on the flow of fluid through natural porous media for reliable data, it is recommended to perform permeability measurement on a full diameter that contains natural fractures 6 .…”
Section: Laboratory Core Analysismentioning
confidence: 99%